Ostomy-Related Complications - Murken, Douglas R.; Bleier, Joshua I. S. (Clinics in Colon and Rectal Surgery, 2019)
Ileostomy or colostomy formation is an important component of many surgical procedures performed for a wide range of disorders of the gastrointestinal tract. Despite the frequency with which intestinal stomas are created, stoma-related complications remain common and are associated with significant morbidity as well as cost. Some of the most prevalent complications of stoma formation which will be detailed in this article include peristomal skin complications, retraction, stomal necrosis, stomal stenosis, prolapse, bleeding, dehydration from high ostomy output, and parastomal hernia. The authors will review these common complications, detail means to avoid or prevent them, and outline recommendations for management.
Keywords: ileostomy; colostomy; complications